Analisis Strategi Komunikasi Digital Pengelolaan Eko-Tourism Berkelanjutan dalam Konservasi Keanekaragaman Hayati dan Pemberdayaan Masyarakat Lokal di Kampung Orchid Kemuning - Dian Deliana; Sujatmiko Sujatmiko; Erwin Purbosaputro; Suyamto Suyamto; Dwi Cahyono; Suci Nur Fatmawati (MASALIQ, 2026)
The transformation of destination management in Kampung Orchid Kemuning is grounded in the need to create synergy between digital marketing, community governance, and conservation education so that social, economic, and ecological sustainability can be achieved simultaneously. This study aimed to analyze effective digital communication strategies in the management of community-based ecotourism, particularly in relation to strengthening digital literacy, improving content quality, developing organizational structures, designing tourism products, and examining their impact on conservation and local economic empowerment. A mixed-methods approach was employed by combining field observation, pretest and posttest of digital literacy, in-depth interviews with managers and residents, and documentation analysis of training activities. The findings show a significant increase in understanding of digital marketing concepts, improved ability to produce visual content, and greater consistency in managing the destination’s social media. The development of five thematic tour packages resulted in tourism products that are more marketable and relevant for diverse visitor segments, while simultaneously strengthening organizational structures, enhancing service responsiveness, and fostering a culture of continuous capacity building at the community level. In addition, the study identified positive socio-economic impacts, including increased community participation in the tourism value chain and higher self-efficacy in digital content production that supports conservation efforts and local empowerment. These findings confirm that integrating digital communication with tourism product management is an effective strategy for strengthening the sustainability of community-based ecotourism.